The repetition of originality : on the question of association between late antique ‘Gnostics’ and the medieval Kabbalah : an argument for a revised methodology - Goldstein, B (2013)
This thesis aims to provide a critique of the conclusions of Gershom Scholem regarding the potential for ‘Gnostic’-Kabbalistic filiation, and to establish whether, in light of the available evidence, Scholem’s arguments (which have yet, to my mind, to be sufficiently challenged) can be reasonably supported. I strive to offer an arguably clearer definition of the relevant taxonomic terms than is often presented in scholarly analyses of this question, whilst also arguing for the applicability to this debate of certain pertinent methodological approaches drawn from the wider school of comparative mythology. As such, I also attempt to establish a clear methodology for judging the probability of the genetic descent of one ‘system’ from another, viz. that perhaps the most logical method for assessing potential similarities between different ‘systems’ is to assume in the first instance that all correspondences identified are essentially coincidental, dismissing this assumption only if one can identify a high level of exactness in these comparisons (such as would render pure coincidence relatively improbable) and/or establish a secure chain of transmission between two sources, a chain which renders the transmission of ideas not only possible but indeed probable. Applying this methodology to certain potential routes by which second century ‘Gnostic’ thought might have been transmitted to the origin point of the medieval Kabbalah, I attempt both to demonstrate the wider applicability of such a methodology beyond the narrow question of ‘Gnostic’-Kabbalistic relationships, and to illustrate the serious difficulties with advancing any of these potential routes as a reliable source for the transmission of ‘Gnostic’ ideas to the Kabbalah. Rather, I argue that it may be more logically defensible, in the absence of clear source evidence, to ascribe such correspondences as are located purely to coincidence, albeit a coincidence perhaps somewhat tempered by certain observations regarding the relative ubiquity of certain concepts and modes of thought.